2011
DOI: 10.1088/0004-637x/736/2/158
|View full text |Cite
|
Sign up to set email alerts
|

CHANDRAANDHSTSTUDIES OF THE X-RAY SOURCES IN GALACTIC GLOBULAR CLUSTER M92

Abstract: We present the analysis of two observations of M92 taken with the Chandra X-Ray Observatory. We combined the two data sets with a total exposure of ∼52 ks. With the combined observation, we detected 10 X-ray sources inside the half-mass radius (1. 02), five of which are inside the core radius (0. 26) of M92. The luminosities of the 10 sources are roughly within the range of 10 30 -10 32 erg s −1 assuming cluster memberships. The background estimation suggests 7-8 cluster members and 2-3 background galaxies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Clusters where multiple identifications of CVs in GCs have been made as counterparts to X-ray sources include 47 Tuc (E03a; E03b; Beccari et al 2014), NGC 6752 (Pooley et al 2002;Thomson et al 2012), NGC 6397 Cohn et al 2010), M30 (Lugger et al 2007), NGC 2808 (Servillat et al 2008), M71 (Huang et al 2010), M80 (Dieball et al 2010), M92 (Lu et al 2011), NGC 6388 (Maxwell et al 2012), and ω Cen (Cool et al 2013). These studies have shown the effectiveness of this technique and have revealed different characteristics of CVs in GCs.…”
Section: Introductionmentioning
confidence: 93%
“…Clusters where multiple identifications of CVs in GCs have been made as counterparts to X-ray sources include 47 Tuc (E03a; E03b; Beccari et al 2014), NGC 6752 (Pooley et al 2002;Thomson et al 2012), NGC 6397 Cohn et al 2010), M30 (Lugger et al 2007), NGC 2808 (Servillat et al 2008), M71 (Huang et al 2010), M80 (Dieball et al 2010), M92 (Lu et al 2011), NGC 6388 (Maxwell et al 2012), and ω Cen (Cool et al 2013). These studies have shown the effectiveness of this technique and have revealed different characteristics of CVs in GCs.…”
Section: Introductionmentioning
confidence: 93%
“…A number of studies have looked for accreting binaries through emission lines searches in GCs (e.g. Pooley et al 2002;Kong et al 2006;Bassa et al 2008;Cohn et al 2010;Lu et al 2011). The GC 47 Tucanae is definitely one of the most promising targets for this kind of investigation, since it harbours a crowded zoo of stellar exotica, including BSSs, LMXBs and candidate CVs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have been used to identify numerous optical/UV counterparts in 47 Tuc (references above) and in numerous other clusters (e.g. Grindlay et al 2001a;Pooley et al 2002b;Kong et al 2006;Bassa et al 2008;Lu et al 2011;Cohn et al 2010;Cool et al 2013).…”
mentioning
confidence: 99%